Analyzing Land Suitability for Housing in Bekasi Regency: Managing Farmland Conversion During Urban Growth - Herlawati Herlawati; Rahmadya Trias Handayanto (LPPM Universitas Islam 45 Bekasi, 2024)
Bekasi Regency is a buffer area for Jakarta and is part of the Jakarta Metropolitan Region (JMR). Along with Karawang, this region is a major rice producer, but it is currently experiencing significant land conversion from agriculture to residential and industrial uses. Preventing this conversion is very challenging due to the high population growth in the area. To address this issue, this study aims to conduct a suitability analysis to identify areas that are unsuitable for agricultural land but still suitable for residential purposes. The factors considered in the suitability analysis include slope, distance to roads, distance to residential areas, distance to facilities and infrastructure, and distance to rivers and irrigation systems. The results of the study identify areas that are unsuitable for agriculture, allowing local governments to focus on these areas as potential sites for new residential developments. The location is situated in the southern part of Bekasi Regency, specifically in the Cikarang area and its surroundings.